Implementation of broad screening with Ebola rapid diagnostic tests in Forécariah, Guinea - Frantz Jean Louis; Jennifer Y. Huang; Yacouba K. Nebie; Lamine Koivogui; Gayatri Jayaraman; Nadine Abiola; Amanda Vansteelandt; Mary C. Worrel; Judith Shang; Louise B. Murphy; David L. Fitter; Barbara J. Marston; et al. (AOSIS, 2017)
Background: Laboratory-enhanced surveillance is critical for rapidly detecting the potential re-emergence of Ebola virus disease. Rapid diagnostic tests (RDT) for Ebola antigens could expand diagnostic capacity for Ebola virus disease. Objectives: The Guinean National Coordination for Ebola Response conducted a pilot implementation to determine the feasibility of broad screening of patients and corpses with the OraQuick® Ebola RDT. Methods: The implementation team developed protocols and trained healthcare workers to screen patients and corpses in Forécariah prefecture, Guinea, from 15 October to 30 November 2015. Data collected included number of consultations, number of fevers reported or measured, number of tests performed for patients or corpses and results of confirmatory RT-PCR testing. Data on malaria RDT results were collected for comparison. Feedback from Ebola RDT users was collected informally during supervision visits and forums. Results: There were 3738 consultations at the 15 selected healthcare facilities; 74.6% of consultations were for febrile illness. Among 2787 eligible febrile patients, 2633 were tested for malaria and 1628 OraQuick® Ebola RDTs were performed. A total of 322 OraQuick® Ebola RDTs were conducted on corpses. All Ebola tests on eligible patients were negative. Conclusions: Access to Ebola testing was expanded by the implementation of RDTs in an emergency situation. Feedback from Ebola RDT users and lessons learned will contribute to improving quality for RDT expansion.